IMPLEMENTASI KEBIJAKAN PENGEMBANGAN E-GOVERNMENT - Said Abdul Aziz (Universitas Riau, 2016)
Implementation of e-Government Development. his study aims to identify and explainwhy the implementation of e-Government development policies in the Departemen of Library,Archives, and Documentation (BPAD) is not effective, and the factors that influence theimplementation of e-Government development policies in BPAD Riau Province. The method used inthis research is descriptive qualitative approach. Supported by the theory developed by Daniel A.Mazmanian and Paul A. Sabatier related Implementation Framework Analysis Model to explain theprocess and policy implementation. For more detailed information about the factors that affect theimplementation of the policy, the author refers to the theory of George C. Edward III. The studyconcluded that the implementation of e-Government Policy in BPAD Riau Province has not runeffectively. Ideally, an established policy should be a policy derived at least in the least internaloperating organization that has the power and the rule. Factors that influence the implementation ofe-Government policy BPAD Riau Province including the Communications factor of policymakersdown in the form of guidelines and technical guidelines. Resource factors namely the dimension ofits human resources in terms of quality and quantity is low. Disposition is the understanding of thefactors related to implementing agencies understand that this policy is merely an appeal and notbinding. Factor structure of the bureaucracy no one has successfully developed specifically relatedfield or officials responsible for implementation of e-Government policy in BPAD Riau Province.